2018
DOI: 10.3390/su11010035
|View full text |Cite
|
Sign up to set email alerts
|

Composition of a Soil Organic Carbon Increment under Different Vegetable Cultivation Patterns: A Study Using Three SOC Pools

Abstract: Previous studies suggest that vegetable cultivation increases soil organic carbon (SOC) storage. However, how stable the SOC increment is, and how greenhouse cultivation contributes to the SOC increment in terms of quantity and stability, remains unclear. Soil samples were taken from three typical vegetable cultivation pattern fields: open field (OF), seasonal greenhouse (SG), and permanent greenhouse (PG), as well as adjacent non-vegetable fields. Three conceptual SOC pools, including active (C a ), slow (C s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…This study demonstrated that the SOC contents of various protected cultivation years were all lower than ck, decreasing year by year. This was contrary to the results of previous studies 20,21 , but similar to the results of Song et al 22 . It may be due to the small amount of organic fertilizer applied and a small return of plant residues to soil in this area.…”
Section: Discussioncontrasting
confidence: 65%
“…This study demonstrated that the SOC contents of various protected cultivation years were all lower than ck, decreasing year by year. This was contrary to the results of previous studies 20,21 , but similar to the results of Song et al 22 . It may be due to the small amount of organic fertilizer applied and a small return of plant residues to soil in this area.…”
Section: Discussioncontrasting
confidence: 65%
“…Greenhouse cultivation has developed rapidly in recent years in China [1], and by 2017, the area under greenhouse cultivation reached 3.7 Mha [2]. Due to the enclosed environment, greenhouse cultivation cannot utilize natural precipitation.…”
Section: Introductionmentioning
confidence: 99%